2021
DOI: 10.3389/fphar.2020.524113
|View full text |Cite
|
Sign up to set email alerts
|

Taking Sleeping Pills and the Risk of Chronic Kidney Disease: A Nationwide Population-Based Retrospective Cohort Study

Abstract: Background: Sleeping disorder has been associated with chronic kidney disease (CKD); however, the correlation between sleeping pills use and CKD has not been investigated in-depth yet. This study elucidated the potential association of sleeping pill use with the risk of CKD and CKD progression to end-stage renal disease (ESRD) requiring dialysis.Methods: This study was based on a population-based cohort that included 209,755 sleeping pill users among 989,753 individuals. After applying the exclusion criteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Diazepam is a common sedative-hypnotic drug in clinical settings, and the ADRs described in SPC include drowsiness, fatigue, muscle weakness, urinary retention, or incontinence. A nationwide population-based retrospective cohort study showed that diazepam had a significant correlation with increased chronic kidney disease risk in the population aged >18 years old (adjusted hazard ratio (HR) = 1.627, 95 CI%:1.527-1.736) (Liao et al, 2020). One of the possible mechanisms is that propylene glycol is contained in parenteral formulations of diazepam, which may cause AKI and proximal tubule injury (Cawley, 2001).…”
Section: Potential New Signalsmentioning
confidence: 99%
“…Diazepam is a common sedative-hypnotic drug in clinical settings, and the ADRs described in SPC include drowsiness, fatigue, muscle weakness, urinary retention, or incontinence. A nationwide population-based retrospective cohort study showed that diazepam had a significant correlation with increased chronic kidney disease risk in the population aged >18 years old (adjusted hazard ratio (HR) = 1.627, 95 CI%:1.527-1.736) (Liao et al, 2020). One of the possible mechanisms is that propylene glycol is contained in parenteral formulations of diazepam, which may cause AKI and proximal tubule injury (Cawley, 2001).…”
Section: Potential New Signalsmentioning
confidence: 99%